1978
DOI: 10.33584/jnzg.1978.40.1519
|View full text |Cite
|
Sign up to set email alerts
|

Perennial Ryegrass Cultivars

Abstract: In the period 1973-77, 71% of pasture grasses certified in New Zealand were perennial ryegrasses. Data from one of the major seed merchants showed that during 1977-8 Ruanui comprised over 70% of the retail sales of perennial ryegrass cultivars, while Nui (17%) and Ariki (10%) were also important. Comparative production data between the New Zealand bred cultivars, some overseas cultivars and some uncertified local populations are presented. Overseas cultivars are generally inferior to New Zealand cultivars but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The superiority of Nui and Ellett was largely achieved through greater total productivity of pastures in the autumn months of March, April and May, with Ellett pastures exhibiting exceptional growth rates in December-January under higher fertility conditions. The superior autumn performance of Nui is a characteristic reported by previous workers (Baars et al, 1976, Lancashire et al, 1979.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The superiority of Nui and Ellett was largely achieved through greater total productivity of pastures in the autumn months of March, April and May, with Ellett pastures exhibiting exceptional growth rates in December-January under higher fertility conditions. The superior autumn performance of Nui is a characteristic reported by previous workers (Baars et al, 1976, Lancashire et al, 1979.…”
Section: Discussionsupporting
confidence: 75%
“…Grasslands 'Ruanui' represents the original selection of southern Hawkes Bay and Poverty Bay ecotypes which formed the basis of NZ Certified Perennial ryegrass (Corkill et al 1981). Several reports have compared the relative merits of Nui and Ruanui swards and highlight the greater autumn recovery growth of Nui and its superior persistence (Baars et al, 1976, Lancashire et al 1979).…”
Section: Introduction Perennial Ryegrassmentioning
confidence: 99%
“…These so called "hybrid" cultivars were the first attempt to increase cool season growth of New Zealand cultivars to a level compatible with New Zealand's mid latitude mild oceanic climate. Germplasm Introduction Considerable germplasm has been introduced since the early colonial introductions, mainly of commercial material, and the results generally confirm the observations of Saxby (1934), Rumball & Armstrong (1974) and Lancashire et al (1979). They conclude that imported northern European germplasm is not well adapted to New Zealand, lacking winter growth and often exhibiting susceptibility to crown or stem rust (Puccinia coronata and P. graminis).…”
Section: Early Plant Breeding Prior To 1960mentioning
confidence: 74%
“…Over the next 30 years a number of experiments showed that local ecotypes that had developed in the permanent pasture regions of New Zealand were superior to British and European commercial lines and to "false perennials" commonly sown and harvested in the cropping districts (as outlined in the reviews by Corkill 1958, Rumball 1983, Easton 1983and Burgess & Easton 1986. Further experiments over the next 60 years have continued to note the poor performance of overseas cultivars in New Zealand (McLeod 1974, Rumball & Armstrong 1975, Lancashire et al 1979.…”
Section: Initial Introductions and Strain Identificationmentioning
confidence: 99%
“…The importance of soil type has been demonstrated by Radcliffe (1979) who showed that the general pattern of pasture production on a perennial ryegrass/white clover sward on dry The use of annual and biennial ryegrasses (Lolium spp.) and subterranean clover for cool season growth and cocksfoot (Dacty-Zis glomerafa L.), lucerne, and to a lesser extent red clover (T. pratense L.) to combat dry summer conditions in these areas is well established, while there appears to be considerable potential for the use .,of species such as phalaris (Rumball, 1969)) tall fescue (Goold and Hupkens van der Elst, 1980), prairie grass (Bromus wildenowii Kunth) (Lancashire, 1978)) Lotus cornicu-Zatus (Charlton et al, 1978), and more drought-tolerant and persistent perennial ryegrasses (Lancashire et al, 1979). Some of these plant types will also have a very useful role in areas which are generally regarded as having less of a soil moisture deficit problem than the eastern half of the country.…”
Section: Soil M Oisture D Eficitsmentioning
confidence: 99%